Enlarged subarachnoid space on cranial ultrasound in preterm infants: Neurodevelopmental implication - Yum, Sook Kyung (Sci Rep, 2019)
The role of enlarged subarachnoid space (ESS) in preterm infants has not been described in concrete. We aimed to evaluate whether ESS should be considered a risk factor potentially associated with adverse neurodevelopmental outcomes in prematurity. Electronic medical records of 197 preterm infants (median 32.1 weeks' gestation) including cranial ultrasound (cUS) images, head circumferences, and Korean Developmental Screening Tests for Infants and Children (K-DST) results at 18–24 months corrected age were reviewed. The clinical characteristics and K-DST results were compared in infants with and without ESS (sinocortical width > 3.5 mm). A multivariable logistic regression analysis was performed to identify potential risk factors associated with positive K-DST results. At a median corrected age of 39.0 weeks, 81/197 (41.1%) infants presented ESS. A significantly greater percent of infants in the ESS group screened positive on the K-DST than in the no ESS group (27.2% vs 12.1%, p = 0.007). Within the ESS group, micro-/macrocephaly at term-equivalent age was not different with regard to the K-DST results. From the multivariable logistic regression analysis, gestational age (p = 0.016, OR = 0.855, 95% CI = 0.753–0.971) and ESS (p = 0.019, OR = 1.310, 95% CI = 1.046–1.641) were two significant risk factors associated with positive K-DST results. ESS identified on cUS at term-equivalent age in preterm infants is associated with possible developmental delays. Macrocephaly at term-equivalent age does not guarantee a benign prognosis. Future studies are required to verify ESS as a potential marker for neurodevelopmental delay in preterm infants.